Investigating Instrumental Values of The Main Character in Moana 2 Movie: A Literary Analysis - Pakpahan, Sirintin; Siahaan, Safnidar; Wilany, Eka (Journal of Language and Literature Studies, 2026)
Animated films play a crucial role in conveying moral messages and shaping character, especially for young audiences. Although there have been previous studies examining Moana (2016) from perspectives such as gender roles or cultural representation, there has been a lack of focus on the analysis of instrumental values, especially for the sequel, Moana 2. Therefore, this study aims to identify the instrumental values represented by the main character, Moana, in Moana 2, while analyzing how these values are reflected through the narrative and her interactions with other characters. This study uses a qualitative descriptive approach with content analysis, where the data comes from Moana's dialogues throughout the film, which were coded and interpreted using Rokeach's 1973 instrumental values framework. The results reveal that 17 out of 18 instrumental values are represented. These values are evident in her decision-making process, her leadership role, her way of resolving conflicts, and her interpersonal interactions, which show that these values serve as ethical guidelines that shape her character development. Ultimately, the conclusion is that Moana 2 depicts Moana as a morally mature leader, with her instrumental values integrated into the storyline, thereby reinforcing the function of animated films as an effective tool for character education and moral development.